The Construction Countermeasures of Shallow-Buried Small Spacing Tunnel Undercrossing Cultural Relic Buildings: A Case Study - Li Wan; Jiajia Shen; Changan Zhang; Zanquan Lin; Hu Zhang (Advances in Civil Engineering)
Based on the background of the reconstruction project from Changqing Chenzhuang-Pingyin section of G220 east-deep line in China, a special tunnel structure and construction plan was carried out according to the construction measures of the shallow-buried small spacing tunnel passing underneath cultural relic buildings, and a comprehensive deformation control scheme of “CRD construction method single-arm excavation + surface grouting prereinforcement + advanced large pipe shed presupport” was put forward. The results of numerical simulation and on-site construction monitoring showed that the overall deformation of aqueduct foundation generally increases first, then decreases and increases again, and finally tends to be stable. The effects of surface grouting prereinforcement and advance large pipe shed presupport are obvious. The comprehensive deformation control scheme can ensure the safety of the existing construction and meet the safety prevention and control requirements.